2019
DOI: 10.1186/s12905-019-0720-7
|View full text |Cite
|
Sign up to set email alerts
|

Douching practices among women in the Bolgatanga municipality of the upper east region of Ghana

Abstract: BackgroundVaginal douching is a common practice among women all over the world. Women douche for various reasons, despite evidence indicating the harmful health effects of the practice. There is lack of data on the practice in Ghana but health behaviors like vaginal douching may be influenced by differences in culture and geography. Therefore, this study sought to assess prevalence and predictors of vaginal douching practices among women of the Bolgatanga Municipality of Ghana.MethodsThis cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…Interestingly, a previous study conducted in 2019 in the Northern part of Ghana reported a slightly lower prevalence of douching (66.5%) compared to the current study's findings 15 . This suggests that douching practices may vary among different regions or populations within Ghana.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, a previous study conducted in 2019 in the Northern part of Ghana reported a slightly lower prevalence of douching (66.5%) compared to the current study's findings 15 . This suggests that douching practices may vary among different regions or populations within Ghana.…”
Section: Discussioncontrasting
confidence: 83%
“…A representative sample of women within the community was selected using a random sampling technique to ensure the generalizability of the findings. Using a prevalence of 67.7% 15 …”
Section: Methodsmentioning
confidence: 99%
“…In our study, 33 (31.4%) of the women included in our study stated to have vaginal douche after sexual intercourse, 10 women (9.5%) at the end of menstrual bleeding, 47 women (44.8%) at every bath, 15 women (14.3%) every time when they make their toilet. A relevant study shows that 60% of the women having vaginal douche stated to have vaginal douche to feel clean and hygienic themselves [22]. Another relevant study base on the reasons for women's having vaginal douche on two conceptual models.…”
Section: Discussionmentioning
confidence: 99%
“…72 (68.6%) of the women included in our study stated to use only water during vaginal douching, 18 (17.1%) women water and soap, 15 women shower gel. The relevant studies show that the most widely used product for vaginal douching is water [7,22,24]. In addition to water, a great variety of materials existing from the thought of making oneself feel good, ranging from commercial materials to natural and herbal ones, are used.…”
Section: Discussionmentioning
confidence: 99%
“…For many women, vaginal cleanliness is associated with a sense of well-being and protection from sexually transmitted infections. In Ghana (Ziba et al, 2019), women reported douching with lemon juice, antiseptics, and vinegar for the purposes of cleanliness.…”
Section: Cross-cultural Intravaginal Practices and Health Implicationsmentioning
confidence: 99%